India Leads Developing Nations in Private Sector Investment : But the Region Needs More Investment to Meet Demands - Harris, Clive (World Bank, Washington, DC, 2012)
India has had the most success attracting more private investment in infrastructure in 2006 than any other developing country. Long-standing policies in most other South Asian countries are beginning to bear fruit as well. Nevertheless, delivering the infrastructure services needed to sustain and accelerate growth in South Asia remains a major challenge. Estimates suggest that closing the gap in service provision and meeting future needs will require infrastructure investment in the range of 7 to 8 percent of Gross Domestic Product (GDP) a year. The private sector can do more to help close the region's infrastructure service deficit. But first the region's governments will need to close the infrastructure policy deficit, manifested in many sectors in distorted pricing, poor governance and accountability, and weak financial and operational performance.